Management of severe congenital laryngeal webs – a 12 year review. (July 2016) - de Trey, L.A.; Lambercy, K.; Monnier, P.; Sandu, K.
Abstract: Objective: The aim of this study was to investigate respiratory and voice outcomes after open surgery for severe congenital laryngeal web. Methods: Included were all patients treated for severe congenital glottic web (Cohen type 3 and 4) between 2002 and 2014. Demographic data, symptoms, endoscopic findings, type of operation, outcome and complications were analyzed. Open surgery was performed with division of the web and enlargement of the subglottis by a laryngotracheal reconstruction or an extended partial cricotracheal resection. Results: Fourteen patients were included. Information on the pre-operative voice was available in 11 patients. Aphonia was present in 6 patients (55%), dysphonia was severe in 1 (9%), moderate in 2 (18%) and mild in 2 (18%). Median age at operation was 19.3 months. As a first line treatment, laryngotracheal reconstruction was performed in 12 patients, and an extended partial cricotracheal resection in 2. Median follow-up was 9.5 months. All patients were successfully decannulated in a median time of 4 months after first surgery. Voice was improved in 10/11 (91%). Post-operatively, 3 patients (27%) had good voice. Dysphonia was severe in 2 (18%), moderate in 3 (27%) and mild in 3 patients (27%). Conclusion: Open surgery for Cohen type 3 and 4 glottic web allowed establishing a patent airway with successful decannulation in all cases. Quality of voice was improved in 91%, however, voice results were variable. In our opinion a delicate operative technique described in the paper is important for optimal voice results.